Porous silicon-based negative electrode material and preparation method thereof

The preparation of porous silicon-based anode material through microelectronic printing technology solves the problem that silicon-based anode material is prone to break during charging and discharging, and achieves high specific capacity and excellent cycling performance. It is suitable for large-scale production and exhibits high capacity retention under different working conditions.

CN119725511APending Publication Date: 2025-03-28NINGXIA UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411915775.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing porous silicon-based anode materials are prone to rupture during charging and discharging, resulting in rapid attenuation of battery performance. The preparation process is costly and the production technology is complex, and there is still room for improvement in the cycle capacity retention rate and specific capacity.

Method used

Microelectronic printing technology is used to prepare porous silicon-based negative electrode materials, and the ultrasonic dispersion of nano-silicon powder in DMF, the addition of PAN and PVP and stir at a constant temperature. Then, it is printed onto the copper foil by using a microelectronic printer, and vacuum drying, pre-oxidation and calcining treatment is carried out to form a porous structure to relieve the stress of silicon expansion.

Benefits of technology

It achieves high specific capacity and excellent cycling performance. The electrode capacity retention rate reaches 90% after 100 cycles, and the first circle capacity is as high as 1528mAh g-1, and is suitable for switching operation under different magnification conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725511A_ABST
    Figure CN119725511A_ABST
Patent Text Reader

Abstract

The invention discloses a porous silicon-based negative electrode material and a preparation method thereof, and belongs to the technical field of electrochemistry. The preparation method of the porous silicon-based negative electrode material comprises the following steps: firstly, adding nano silicon powder into DMF (Dimethyl Formamide), sealing with a glass bottle, putting into an ultrasonic nano dispersion instrument for ultrasonic dispersion, then respectively adding PAN (Polyacrylonitrile) and PVP (Polyvinyl Pyrrolidone), stirring in a constant-temperature state of 40-80 DEG C, finally stirring in a normal-temperature state, and printing on a copper foil by using a microelectronic printer after stirring is completed; then putting the prepared electrode into a vacuum drying oven for vacuum drying, then putting the electrode into a tubular furnace, carrying out heat preservation in an air atmosphere, and then heating for pre-oxidation; and finally, punching the pre-oxidized electrode into a wafer, putting the wafer into a tubular furnace, and calcining twice at different temperatures in an Ar atmosphere. By adopting the porous silicon-based negative electrode material and the preparation method thereof, the technical problems of high preparation cost, complex production technology and serious cracking after multiple cycles of the porous silicon-based negative electrode material in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a porous silicon-based negative electrode material and a preparation method thereof. Background Art

[0002] In the context of today's global energy transformation, high-performance lithium-ion batteries have become the key to promoting the development of new energy vehicles and renewable energy storage systems. As a cutting-edge battery material technology, porous silicon-based anode materials are gradually attracting widespread attention from the research and industry circles due to their significantly improved energy storage capacity and battery performance. The reason why porous silicon-based anode materials are valued is mainly because silicon as anode material is much higher than traditional graphite (372mAhg -1 ) has a higher specific capacity (4200mAhg -1 ). In theory, the lithium ion storage capacity of silicon is nearly ten times that of graphite. However, the huge volume effect of silicon during the charge and discharge process will lead to the rupture of the material and the rapid decay of battery performance. Therefore, the development of a porous negative electrode material with a three-dimensional conductive network and good porosity is of great significance for improving the performance of lithium-ion batteries.

[0003] In the development process of porous silicon-based negative electrode materials, researchers have proposed different preparation methods, such as sol-gel method, template method, chemical vapor deposition method, etc., all in order to control the microstructure of the material and optimize its performance. By regulating the pore size, porosity and surface chemical properties of the porous structure, the lithium ion diffusion efficiency and electrochemical activity of the material can be significantly improved. In addition, surface modification techniques such as carbon coating or metal oxide coating are also used to further improve the conductivity and chemical stability of the material. Despite this, there are still some technical and economic barriers to the practical application of porous silicon-based negative electrode materials. For example, the high cost of the preparation process, the technical complexity of large-scale production, and the serious cracking of electrode materials after multiple cycles. Microelectronic printing technology is known for its high precision and high efficiency. It can perform precise material deposition at the micron or even nanometer scale and has the advantage of low cost. The inventive point of this application is to provide a new method for preparing porous silicon-based composite materials, which uses microelectronic printing technology to improve the precision and efficiency of negative electrode material preparation while having mass production capabilities.

[0004] Patent CN 118712345A discloses a silicon-based negative electrode material and a preparation method thereof. The silicon-based negative electrode material is modified by coating the silicon-based core with a specific material, and an artificial SEI film is coated on the surface of the silicon-based core, so that the silicon-based negative electrode material has excellent electrical conductivity and lithium ion conductivity, and can effectively inhibit the volume expansion of the silicon-based material. However, the capacity retention rate is 75.5-86.8% after the battery is cycled 50 times, and the capacity retention rate still needs to be improved. Patent CN 118782758A discloses a silicon-based composite negative electrode material and a preparation method thereof. The prepared silicon-based composite material has a first coulombic efficiency of 93.04% at a current density of 0.1C, but the first charge and discharge specific capacity is 588.8mAh g -1 and 632.8mAh g -1 In summary, how to suppress the volume effect of silicon during the charge and discharge process and improve the capacity retention rate and charge and discharge specific capacity of silicon-based negative electrodes in lithium-ion batteries during the cycle process is still a very important issue. Summary of the invention

[0005] The purpose of the present application is to provide a porous silicon-based negative electrode material and a preparation method thereof. The preparation method of the electrode material is simple, is less affected by the environment, has a high charge and discharge specific capacity and cycle life, is used for the production of silicon-based negative electrode materials for lithium-ion batteries, can improve the electrochemical performance of the battery, and has broad application prospects.

[0006] The present application provides a method for preparing a porous silicon-based negative electrode material, comprising the following steps:

[0007] Step 1: Add nano silicon powder into DMF, seal it with a glass bottle and put it into an ultrasonic nano-disperser for ultrasonic dispersion, then add PAN and PVP respectively, and stir at a constant temperature of 40-80°C, and finally stir at room temperature. After stirring, print it on copper foil using a microelectronic printer.

[0008] Step 2: Place the electrode printed in step 1 into a vacuum drying oven for vacuum drying, then place it into a tubular furnace, keep it warm in an air atmosphere, and then heat it for pre-oxidation.

[0009] Step 3: Punch the pre-oxidized electrode obtained in step 2 into discs, put them into a tube furnace, and calcine them at two different temperatures in an Ar atmosphere.

[0010] Preferably, in step 1, the ultrasonic time is 2-6 hours.

[0011] Preferably, in the electrode printed in step 1, the mass ratio of nano-silicon, DMF, PVP and PAN is 1:43:3:3.

[0012] Preferably, in step 1, the stirring time is 5 hours at a constant temperature of 40-80°C; and the stirring time is 10 hours at room temperature.

[0013] Preferably, in step 2, the vacuum drying temperature is 90-120°C, and the drying time is 6-12h; the insulation temperature in the tubular furnace is 90-150°C, the heating rate is 1-3°C / min, and the insulation time is 1-3h; during pre-oxidation, the temperature in the tubular furnace is 200-300°C, the heating rate is 1-3°C / min, and the pre-oxidation time is 1-3h.

[0014] Preferably, the first heating temperature under Ar atmosphere is 350-450°C, the heating rate is 3-6°C / min, and the holding time is 1-3h; the second heating temperature is 600-1000°C, the heating rate is 3-6°C / min, and the calcination time is 1-3h.

[0015] The present application provides a porous silicon-based negative electrode material prepared by the above-mentioned preparation method.

[0016] The present application also provides a battery comprising the above-mentioned porous silicon-based negative electrode material, wherein the twice calcined electrode, positive electrode disc, electrolyte and battery shell obtained in step one are put into a glove box for assembly, and then left to stand for 24 hours after assembly.

[0017] Therefore, the present application provides a method for preparing a porous silicon-based negative electrode material, which has the following beneficial effects:

[0018] 1. The electrode material prepared by this method is porous, which can provide a certain space for the expansion of silicon during the charge and discharge process, so that the electrode can maintain no cracking or very small cracking during the cycle process, and has high specific capacity and excellent cycle performance.

[0019] 2. The preparation method of electrode materials is microelectronic printing, which has fast printing speed and high precision. Compared with electrospinning and other technologies, it has the ability to be mass-produced.

[0020] 3. The electrode material has high first cycle capacity and reversible capacity retention ratio. The first cycle capacity is 1528mAh g at a current density of 0.1Ag-1 -1 After 100 cycles of charge and discharge, the specific capacity is 1081 mAh g -1 , the reversible capacity was maintained at 93%.

[0021] 4. It has a high capacity retention rate. After 100 cycles, the capacity is increased from the initial 1203mAh g -1 Decay to 1081mAh g -1, the capacity retention rate is 90%. This is due to the large pore size and high porosity of the porous structure of the material, which provides enough space for the expansion of silicon, so that the electrode can still maintain a high specific capacity after 100 cycles.

[0022] 5. The capacity recovery rate of the electrode prepared by the present invention is relatively high, and it is suitable for switching operation under different rate conditions. Figure 3 As shown, the electrode still has high capacity after charging and discharging at different current densities. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM image of the electrode material prepared in the present invention after 100 cycles;

[0024] Figure 2 This is a constant current-constant voltage charging and constant current discharging cycle performance diagram of the electrode material prepared in the present invention;

[0025] Figure 3 The figure is a rate performance diagram of the electrode material prepared in the present invention at different current densities. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is further illustrated by the following examples.

[0027] Example 1

[0028] A method for preparing a porous silicon-based negative electrode material comprises the following steps:

[0029] (1) First, 0.11 g of nano-silicon powder was added to 5 ml of DMF, which was sealed in a glass bottle and then placed in an ultrasonic nano-dispersor for ultrasonic dispersion for 3 h. Then, 0.33 g of PAN and 0.33 g of PVP were added respectively and stirred at a constant temperature of 60 °C for 5 h. Finally, the mixture was stirred at room temperature for 10 h. After stirring, it was printed on copper foil using a microelectronic printer. The printing speed was 1 mm / s, the needle height was 49.7 mm, the printing pressure was 10 kPa, and the substrate temperature was 50 °C.

[0030] (2) The prepared electrode was then placed in a vacuum drying oven at 120°C for 8 h, and then placed in a tubular furnace and kept at 120°C (heating rate 1°C / min) for 1 h in an air atmosphere, and then heated to 260°C (heating rate 1°C / min) for pre-oxidation for 2 h.

[0031] (3) The pre-oxidized electrode obtained in (2) was punched into discs and placed in a tubular furnace. The calcination temperature was set to 400°C (heating rate of 5°C / min) under Ar atmosphere and kept at this temperature for 1 h. The temperature was then raised to 800°C (heating rate of 5°C / min) and calcined for 2 h.

[0032] (4) The electrodes, positive electrode discs, electrolyte and battery shell obtained in (3) after the double calcination are put into a glove box for assembly, and then left to stand for 24 hours.

[0033] Figure 1 This is the SEM characterization of the negative electrode material prepared by the present invention after 100 cycles. It can be seen that the electrode has small cracks, but the overall coating is good and the porosity is high. This shows that the prepared material has formed a porous structure, which can provide sufficient space for the expansion of silicon during the charge and discharge process, so that the electrode has good cycle stability and high capacity retention rate.

[0034] Figure 2 This is the constant current-constant voltage charging and constant current discharging cycle performance diagram of the negative electrode material prepared by the present invention. -1 The first charge and discharge specific capacities of the electrodes are 1528 mAh g -1 and 1211mAh g -1 After the first cycle of the electrode, the CE of the second cycle increased to 98%, and then remained at around 98%. It can be clearly seen that the electrode material has a high first cycle capacity and reversible capacity retention ratio. After 100 cycles, the capacity of the electrode increased from the initial 1203mAh g -1 Decay to 1081mAh g -1 , the capacity retention rate is 90%, which shows that the electrode structure of the present invention can well prevent the contact between silicon particles and electrolyte, thereby reducing the deactivation of silicon particles.

[0035] Figure 3 The rate performance test of the electrode material prepared by the present invention under high current density. The current density is set to 0.1A. -1 , 0.2Ag -1 , 0.5Ag -1 , 1.0Ag -1 , 0.1Ag -1 When the current density increases, the electrode capacity increases from 1233mAhg -1 (5th) down to 1114mAh g -1 (15th), 896mAh g -1 (25th), 781mAh g -1 (35th), the capacity loss rate is 36.6%. When the current density is restored to 0.1A -1 When the capacity is 1202mAh g -1 (10th) Restored to 1188mAh g -1(45th), the capacity recovery rate is 93%. It can be seen from the data that the capacity recovery rate of the electrode prepared by the present invention is relatively high, which indicates that it is suitable for switching work under different rate conditions. At the same time, the high rate capacity loss of the electrode is small, indicating that it is suitable for working under high current density.

[0036] Example 2

[0037] A method for preparing a porous silicon-based negative electrode material and application thereof, comprising the following steps:

[0038] (1) First, 0.11g of nano-silicon powder was added to 7ml of DMF, sealed with a glass bottle and placed in an ultrasonic nano-disperser for ultrasonic dispersion for 3h, then 0.33g of PAN and 0.33g of PVP were added respectively, and stirred at a constant temperature of 60℃ for 5h, and finally stirred at room temperature for 6h. After stirring, it was printed on copper foil using a microelectronic printer. The printing speed was 1mm / s, the needle height was 49.7mm, the printing pressure was 10kPa, and the substrate temperature was 50℃.

[0039] (2) The prepared electrode was then placed in a vacuum drying oven at 90°C for 6 h, and then placed in a tubular furnace and kept at 90°C (heating rate 1°C / min) for 1 h in an air atmosphere, and then heated to 200°C (heating rate 1°C / min) for pre-oxidation for 1 h.

[0040] (3) The pre-oxidized electrode obtained in (2) was punched into discs and placed in a tubular furnace. The calcination temperature was set to 350°C (heating rate 3°C / min) under Ar atmosphere and kept at this temperature for 1 h. The temperature was then raised to 600°C (heating rate 3°C / min) and calcined for 1 h.

[0041] (4) The electrodes, positive electrode discs, electrolyte and battery shell obtained in (3) after the double calcination are put into a glove box for assembly, and then left to stand for 24 hours.

[0042] Example 3

[0043] A method for preparing a porous silicon-based negative electrode material and application thereof, comprising the following steps:

[0044] (1) First, 0.11 g of nano-silicon powder was added to 5 ml of DMF, which was sealed in a glass bottle and then placed in an ultrasonic nano-dispersor for ultrasonic dispersion for 3 h. Then, 0.55 g of PAN and 0.55 g of PVP were added respectively, and stirred at a constant temperature of 60 °C for 12 h. Finally, the mixture was stirred at room temperature for 14 h. After stirring, it was printed on copper foil using a microelectronic printer. The printing speed was 1 mm / s, the needle height was 49.7 mm, the printing pressure was 10 kPa, and the substrate temperature was 50 °C.

[0045] (2) The prepared electrode was then placed in a vacuum drying oven at 120°C for 12 h, and then placed in a tubular furnace and kept at 150°C (heating rate 3°C / min) for 3 h in an air atmosphere, and then heated to 300°C (heating rate 3°C / min) for pre-oxidation for 3 h.

[0046] (3) The pre-oxidized electrode obtained in (2) was punched into discs and placed in a tubular furnace. The calcination temperature was set to 450°C (heating rate 5°C / min) under Ar atmosphere and kept at this temperature for 3 h. The temperature was then raised to 1000°C (heating rate 5°C / min) and calcined for 3 h.

[0047] (4) The electrodes, positive electrode discs, electrolyte and battery shell obtained in (3) after the double calcination are put into a glove box for assembly, and then left to stand for 24 hours.

[0048] Comparative Example 1:

[0049] (1) First, 0.11 g of nano-silicon powder was added to 5 ml of DMF, which was sealed in a glass bottle and then placed in an ultrasonic nano-dispersor for ultrasonic dispersion for 3 h. Then, 0.33 g of PAN and 0.33 g of PVP were added respectively and stirred at a constant temperature of 60 °C for 5 h. Finally, the mixture was stirred at room temperature for 10 h. After stirring, it was printed on copper foil using a microelectronic printer. The printing speed was 1 mm / s, the needle height was 49.7 mm, the printing pressure was 10 kPa, and the substrate temperature was 50 °C.

[0050] (2) The prepared electrode was placed in a vacuum drying oven at 120 °C for 8 h.

[0051] (3) The electrode obtained in (2) was punched into a disc and placed in a tubular furnace. The calcination temperature was set to 400°C (heating rate of 5°C / min) under Ar atmosphere and kept at this temperature for 1 h. The temperature was then raised to 800°C (heating rate of 5°C / min) and calcined for 2 h.

[0052] (4) The electrodes, positive electrode discs, electrolyte and battery shell obtained in (3) after the double calcination are put into a glove box for assembly, and then left to stand for 24 hours.

[0053] Due to the lack of a pre-oxidation step, the stability and microstructural order of the material are poor. The oxygen-containing groups formed on the electrode surface reduce the adsorption of carbon, the degree of pulverization and shedding of the material is more serious than that of Example 1, and the pore structure of the material is not regular enough, and the porosity is relatively low, so that in the subsequent charge and discharge process, the buffer space of some silicon is insufficient, resulting in a decrease in battery capacity and coulombic efficiency.

[0054] Similarly, 0.1Ag -1When the charge-discharge cycle test was carried out at a current density of 1.500 mAh g, the first charge-discharge specific capacity of the electrode of Comparative Example 1 was not as good as that of Example 1. Its first charge-discharge specific capacity was about 1300 mAh g -1 (Compared to 1528 mAhg in Example 1 -1 After the first cycle of the electrode, the coulombic efficiency (CE) increased to about 95%, but in the subsequent cycles, the CE value fluctuated relatively greatly and was difficult to reach and stably maintain around 98% of Example 1. After 100 cycles, the electrode capacity of Comparative Example 1 increased from the initial 1000mAh g -1 Decays to approximately 700mAh g -1 , the capacity retention rate is only about 70%, which is much lower than 90% in Example 1. This shows that: without the key pre-oxidation treatment, the electrode structure is more easily damaged during the cycle due to the volume expansion of silicon, the adsorption capacity of oxygen-containing groups on carbon is reduced, the porosity decreases, resulting in faster capacity decay, and the cycle performance of the electrode is poor.

[0055] Comparative Example 2:

[0056] (1) First, 0.11 g of nano-silicon powder was added to 5 ml of DMF, which was sealed in a glass bottle and then placed in an ultrasonic nano-dispersor for ultrasonic dispersion for 3 h. Then, 0.33 g of PAN and 0.33 g of PVP were added respectively, and stirred at a constant temperature of 60 °C for 5 h. Finally, the mixture was stirred at room temperature for 10 h. After stirring, it was printed on copper foil using a microelectronic printer. The printing speed was 3 mm / s, the needle height was 20 mm, the printing pressure was 15 kPa, and the substrate temperature was 50 °C.

[0057] (2) The prepared electrode was then placed in a vacuum drying oven at 120°C for 8 h, and then placed in a tubular furnace and kept at 120°C (heating rate 1°C / min) for 1 h in an air atmosphere, and then heated to 260°C (heating rate 1°C / min) for pre-oxidation for 2 h.

[0058] (3) The pre-oxidized electrode obtained in (2) was punched into discs and placed in a tubular furnace. The calcination temperature was set to 400°C (heating rate of 5°C / min) under Ar atmosphere and kept at this temperature for 1 h. The temperature was then raised to 800°C (heating rate of 5°C / min) and calcined for 2 h.

[0059] (4) The electrodes, positive electrode discs, electrolyte and battery shell obtained in (3) after the double calcination are put into a glove box for assembly, and then left to stand for 24 hours.

[0060] After changing the printing parameters, the printed electrode is too thick. In this case, the stress distribution inside the electrode becomes uneven. The electrode shows a more obvious uneven thickness phenomenon, and some areas are too thick. This not only destroys the uniform pore structure that should have been there, making the pores of different sizes and poor connectivity, but also causes the stress distribution inside the electrode to be extremely uneven. And during the charge and discharge cycle, this uneven and overly thick electrode structure cannot effectively disperse the stress generated by silicon expansion. Comparative Example 1, the electrode material after 100 cycles was disassembled, and it was found that the overall cracking of the electrode was very serious, with a large number of through cracks, and even material peeling in some areas, which seriously damaged the integrity and conductive network of the electrode.

[0061] Therefore, the present application adopts the above-mentioned porous silicon-based negative electrode material and its preparation method to solve the technical problems of high preparation cost, complex production technology and severe cracking of porous silicon-based negative electrode materials after multiple cycles in the prior art.

[0062] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.

[0063] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a porous silicon-based negative electrode material, characterized in that: The following steps are involved: Step 1: Add nano silicon powder into DMF, seal it with a glass bottle and put it into an ultrasonic nano-disperser for ultrasonic dispersion, then add PAN and PVP respectively, and stir at a constant temperature of 40-80°C, and finally stir at room temperature. After stirring, print it on copper foil using a microelectronic printer. Step 2: Place the electrode printed in step 1 into a vacuum drying oven for vacuum drying, then place it into a tubular furnace, keep it warm in an air atmosphere, and then heat it for pre-oxidation. Step 3: Punch the pre-oxidized electrode obtained in step 2 into discs, put them into a tube furnace, and calcine them at two different temperatures in an Ar atmosphere.

2. The method for preparing a porous silicon-based negative electrode material according to claim 1, characterized in that: In step 1, the ultrasonication time is 2-6 hours.

3. The method for preparing a porous silicon-based negative electrode material according to claim 1, characterized in that: The mass ratio of nano-silicon, DMF, PVP, and PAN in the electrode after printing in step 1 is 1:43:3:

3.

4. The method for preparing a porous silicon-based negative electrode material according to claim 1, characterized in that: In step 1, the stirring time is 4-12 hours at a constant temperature of 40-80°C; and the stirring time is 6-10 hours at room temperature.

5. The method for preparing a porous silicon-based negative electrode material according to claim 1, characterized in that: In step 2, the vacuum drying temperature is 90-120°C, and the drying time is 6-12h; the insulation temperature in the tubular furnace is 90-150°C, the heating rate is 1-3°C / min, and the insulation time is 1-3h; during pre-oxidation, the temperature in the tubular furnace is 200-300°C, the heating rate is 1-3°C / min, and the pre-oxidation time is 1-3h.

6. The method for preparing a porous silicon-based negative electrode material according to claim 1, characterized in that: In step three, the first heating temperature under Ar atmosphere is 350-450°C, the heating rate is 3-6°C / min, and the holding time is 1-3h; the second heating temperature is 600-1000°C, the heating rate is 3-6°C / min, and the calcination time is 1-3h.

7. A porous silicon-based negative electrode material prepared according to the method for preparing a porous silicon-based negative electrode material according to any one of claims 1 to 6.

8. A battery according to claim 7, characterized in that: The porous silicon-based negative electrode material according to claim 7 is included, and the electrode, positive electrode disc, electrolyte and battery shell obtained in step 1 after twice calcination are put into a glove box for assembly, and then left to stand for 24 hours after assembly.

Citation Information

Patent Citations

  • Silicon-based composite negative electrode material and preparation method thereof

    CN118782758A

  • Porous carbon membrane for lithium-sulfur batteries and application of porous carbon membrane

    CN105731416A

  • Carbon-silicon composite material and preparation method and application thereof

    CN107204438A

  • A nano-tubular silicon-based material with a core shell structure and preparation and application thereof

    CN109585808A

  • Nitrogen-doped mesoporous carbon sphere non-metal oxygen reduction catalyst, preparation method and application thereof

    CN109686993A